Applying the Pro-Circular change model to restaurant and retail businesses' preferences for circular economy: evidence from Indonesia. Issue 1 (9th December 2022) - Auwalin, Ilmiawan; , Rumayya; Rahma Sari, Faradilla; Maulida, Saskia Rizqina
Abstract: This study aims to examine the impact of persuasive communication as a behavioral change intervention for the pro-circular behavior of restaurant and retail business actors. The Pro-Circular Change Model (P-CCM) with an extended formulation of the Theory of Planned Behavior is used as the underlying framework. In the analysis, we employ a paired t-test to capture the differences before and after the intervention. We find evidence that behavioral change interventions are relatively effective in altering how individuals view the efforts needed to implement features of a pro-circular economy in their business. We also find that persuasive communication is relatively effective in promoting public awareness about current environmental issues. However, we find no significant impact on behavioral intention to implement circular economy strategies.